Freshwater Ostracoda (Crustacea) of Diyarbakır Province, including a new report for Turkey - (:unkn) unknown (My University, 2011)
Diyarbakır’daki 90 farklı sulak alandan 50 tanesinden 2007 yaz süresince (Temmuz-Ağustos) toplanan ostrakot türleri incelenmiş ve 14 cinse ait toplam 23 tatlı su ostrakot türü tespit edilmiştir. Herpetocypris intermedia Türkiye ostrakot faunası için yeni kayıt olarak rapor edilmiştir. Bunun yanında, 11 tür ise (Ilyocypris decipiens, I. inermis, Eucypris virens, Herpetocypris brevicaudata, Psychrodromus fontinalis, Isocypris beauchampi, Potamocypris similis, P. unicaudata, P. arcuata, Limnocythere stationis, L. inopinata) Diyarbakır için yeni kayıttır. Bazı türlerin coğrafi k dağılımı Türkiye’nin doğu kesimlerine kadar genişletilmiştir. Sonuçlar kozmopolit karaktere sahip türlerin farklı habitatlardaki dağılımının da geniş olduğunu önermektedir.

During the summer (July-August) of 2007, a total of 23 freshwater ostracods belonging to 14 genera were collected from 50 out of 90 diff erent bodies of water in Diyarbakır. Of these 23 fi nds, Herpetocypris intermedia is a new report for Turkish ostracod fauna. In addition, 11 species (Ilyocypris decipiens, I. inermis, Eucypris virens, Herpetocypris brevicaudata, Psychrodromus fontinalis, Isocypris beauchampi, Potamocypris similis, P. unicaudata, P. arcuata, Limnocythere stationis, and L. inopinata) are reported from this city for the first time. The geographical distribution of some species is extended into the eastern parts of Turkey. Our results also suggest that species with cosmopolitan characteristics tend to have a wide distribution within a variety of habitats.
Diyarbakır bölgesinin tatlısu Ostrakotları (Crustacea) ve Türkiye için bir yeni kayıt
Keywords: Biyoloji